Mechanical power losses of full-complement needle bearings of planetary gear sets: Model and experiments. (March 2016) - Talbot, D; Kahraman, A; Stilwell, AW; Singh, A; Napau, I
Full-complement (loose) needle bearings are used widely in automatic transmissions as planetary gear set planet bearings due to their cost advantages and high load-carrying capacity. This study provides theoretical and experimental investigations of the efficiency performance of full-complement needle bearings in a planetary gear set. An experimental setup is introduced to measure planetary gear set power losses. A number of full-complement needle bearing variations as well as a baseline caged needle bearing arrangement are tested within ranges of speed, torque, and oil temperature as well as key bearing parameters such as needle diameter and number of needle rows. A mechanical power loss model of full-complement needle bearings is proposed next. The model employs an elastohydrodynamic lubrication formulation for rolling power losses and includes the effects of needle skewing and needle-to-needle sliding. Predicted mechanical power losses are compared to measurements to assess the accuracy of the model. Results indicate that (i) full-complement needle bearings are consistently less efficient than the corresponding caged-needle baseline design, and (ii) double-row bearings have higher efficiency than their single-row counterparts, while the influence of the needle diameter on power loss is somewhat secondary.